2019
DOI: 10.1088/1755-1315/260/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antioxidant activity of gaharu leaf tea (Aquilaria malaccensis Lamk) as raw material of tea from middle Tapanuli Regency, North Sumatera Province

Abstract: Gaharu (agarwood) grows naturally in Sumatera, especially in Middle Tapanuli regency. The development of knowledge and research about gaharu leaf has been used as raw material for brewed beverage or tea. The purposes of this research were to observe the leaf used as raw material of gaharu leaf tea that grows naturally in Middle Tapanuli by looking at the chemical compound contained in the leaf which function as antioxidant and to know the antioxidant activity and tannin content of the leaf. Gaharu leaf from 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Study about A. malaccensis have been conducted by some researcher, such as: Borah et al (2012) have been studied about new record of leaf spot disease on A. malaccensis Lamk. in India, Shankar (2012) has been studied about effect of seed abortion and seed storage on germination and seedling growth in A. malaccensis, have been studied about development and characterization of polymorphic microsatellites markers in endangered A. malaccensis and genetic diversity and population structure of endangered A. malaccensis, Siah et al (2016) have been studied about transcriptome reveals senescing callus tissue of A. malaccensis, an endangered tropical tree, triggers similar response as wounding with respect to terpenoid biosynthesis, Wong et al (2013) have been studied about characterization of wound responsive genes in A. Malaccensis, Putri et al (2017) have been studied about evaluation of incense-resinous wood formation in agarwood using sonic tomography and Usuluddin et al (2018), have been studied about the growth of A. malaccensis in alluvial soils with different shade and height of seedlings. Research of mapping of land suitability for A. malaccensis in this location has never been conducted, even though, Sei Bingai Sub District, Langkat District, and Biru-biru Sub District, Deli Serdang District, North Sumatera Province are potential location to develop A. malaccensis in North Sumatra Province.…”
Section: Introductionmentioning
confidence: 99%
“…Study about A. malaccensis have been conducted by some researcher, such as: Borah et al (2012) have been studied about new record of leaf spot disease on A. malaccensis Lamk. in India, Shankar (2012) has been studied about effect of seed abortion and seed storage on germination and seedling growth in A. malaccensis, have been studied about development and characterization of polymorphic microsatellites markers in endangered A. malaccensis and genetic diversity and population structure of endangered A. malaccensis, Siah et al (2016) have been studied about transcriptome reveals senescing callus tissue of A. malaccensis, an endangered tropical tree, triggers similar response as wounding with respect to terpenoid biosynthesis, Wong et al (2013) have been studied about characterization of wound responsive genes in A. Malaccensis, Putri et al (2017) have been studied about evaluation of incense-resinous wood formation in agarwood using sonic tomography and Usuluddin et al (2018), have been studied about the growth of A. malaccensis in alluvial soils with different shade and height of seedlings. Research of mapping of land suitability for A. malaccensis in this location has never been conducted, even though, Sei Bingai Sub District, Langkat District, and Biru-biru Sub District, Deli Serdang District, North Sumatera Province are potential location to develop A. malaccensis in North Sumatra Province.…”
Section: Introductionmentioning
confidence: 99%
“…After 5 days the mixture was covered (strained), and washed with 96% ethanol sufficiently up to 2000 mL, then moved in a closed vessel and left in a cool place protected from light for 2 days, then two days later, it was poured and filtered. Macerate was concentrated using a rotary evaporator at a temperature of 40°C until a concentrated macerate was obtained, then was dried using the freeze dryer so that dried extract was obtained (Surjanto et al 2019a).…”
Section: Ethanol Extract Of Agarwood Preparationmentioning
confidence: 99%
“…Also, this decision has taken based on previous research. The results of the antioxidant activity test showed that the ethanol extract of A. malaccensis leaves from Sigiring-giring and S. circles II had IC50 values of 56.985 and 44.382 μg/mL respectively, with strong and very strong antioxidant activity categories (Surjanto et al 2019a). Potential antioxidant compounds can be predicted from the phenolic class, flavonoids, and alkaloids which are polar compounds (Enggiwanto et al 2018).…”
Section: Ic50 (Inhibitory Concentration) Value Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ethyl acetate extract inhibits hemoglobin oxidation (Miniyar et al 2008). In a study of raw tea material from North Sumatra, the leaves were found to have strong antioxidant activities (Surjanto et al 2019). Anticancer and cytotoxic: Aqueous leaf extracts inhibit the cyclophosphamideinduced toxicity in reproductive systems in male rats (Abdul Razak et al 2019).…”
Section: Bioactivitymentioning
confidence: 99%